KEMAMPUAN PROBLEM-SOLVING SISWA SMA DALAM MENYELESAIKAN MASALAH PLSV - Nisa Monika Adinda Juliandini; Dadang Rahman Munandar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this study is to measure the level of problem-solving ability of high school students in solving PLSV material problems. This type of research uses qualitative. The study subjects numbered four high school students in class X. The data was collected through problem tests and described using descriptive methods. The data analysis technique used consists of three paths, namely data reduction, data presentation, and drawing conclusions. Based on the polya problem solving stage, the results of the study are obtained as follows: the first stage obtains 43.75%, the second stage obtains 87.50%, the stage of non-obtaining 62.50%, and the fourth stage obtains 25%. From these results, it can be seen that the stage of re-checking is in the low category with the smallest percentage among others, while the stage of preparing a plan is in the very high category with the highest percentage.